Flowcytometric assessment of platelet microparticles CD41 and CD62P in E/BETA-thalassemia patients in public hospitals in Selangor, Malaysia - Almhanawai, Bahaa Hadi Jaber (2016)
The hypercoagulability complications and an increase in thrombosis risk have been reported in B-thalassemia patients. Despite the fact that the life expectancy of Bthalassemia has been improved, thalassemic patients still suffer from many complications including thrombotic risk. High level of platelet microparticles (PMPs) in the circulation of B-thalassemia patients is believed to be responsible for the presence of hypercoagulability state in B-thalassemia patients. The main objective of this research was to assess the level of platelet microparticles in Hb E/B-thalassemia patients and normal individuals in the Malaysian population. The specific objectives were to determine the level of platelet microparticles CD41 and CD62P in Hb E/Bthalassemia and normal individuals, determine the Annexin-5 level in both, Hb E/Bthalassemia and normal individuals, and to correlate the levels of platelet microparticles with the blood parameters. A case-control study was carried out to assess the level of platelet microparticles in Hb E/beta-thalassemia patients (cases) and normal individuals (control) in the Malaysian population. A convenience sample of 37 patients with Hb E/beta-thalassemia (12 paediatrics and 25 adults) were investigated and compared with 28 normal individuals (3 paediatrics and 25 adults) who were studied in the same period. The samples were analyzed using immunophenotyping application in flow cytometer platform. PMPs were processed and analyzed directly after labeling by BD FACS-CantoIITM flow cytometer (Becton Dickinson, USA), using FlowJo software (version 10.1r1). Platelet microparticles defined as MPs that were smaller than 1.0 μm, had a positive staining for A-5, and exposed platelet-specific markers namely, CD41 and/or CD62P. However, in this research, the mean event of CD62P Vs. A-5 were significantly higher in Hb E/Bthalassemia compared to the normal individuals in the adults group (p= 0.006) respectively. There was a strong association between the phospholipid (PS) and platelet activation markers CD41 and CD62P on the activated platelet cells. In conclusion, platelet microparticles are significantly increased in Hb E/B-thalassemia patients compared to the normal individuals, and there is a strong association between platelet microparticle and some blood parameters.